A Two-Stage Evaluation Framework for Underground Space Development in Green Spaces: A Case Study of Binjiang District, Hangzhou - Qiuxiao Chen; Xiuxiu Chen; Hongbo Li; Xiaoyi Zhang; Geyuan Zhang (Buildings)
In the current context of tight constraints on land resources in major Chinese cities, the development of underground space in green spaces (USGSs) has become an important approach to exploit land use potential and alleviate the contradiction between human and land resources. Evaluating USGS development potential scientifically is crucial for project site selection and improving underground space utilization. However, most studies have focused on underground space as a whole, with limited attention to single land use types, and research on USGSs has mainly concentrated on planning and design. This study proposes a two-stage evaluation framework for urban green spaces, identifying suitable development areas while safeguarding ecological functions. The framework evaluates from “restrictiveness” and “suitability”: first extracting developable green spaces by restrictiveness evaluation and then assessing development potential by suitability evaluation. This approach overcomes traditional methods that disregard prerequisite relationships among factors. A case study in Binjiang District, Hangzhou, showed that small green spaces and connectivity were key limiting factors for the development of USGSs. The proposed framework could provide some degree of reference for future development potential evaluation of USGSs, and the results could provide actionable guidance for high-density built environments similar to Binjiang District.